The association between nutritional status, fruits and vegetables intake and physical activity with academic achievement among school children aged 9-11 years old in Kelantan - Sobri, Nur Syazwina Mohd (Universiti Sains Malaysia, 2016)
The aim of this study was to determine the association between nutritional status, physical activity level and fruit and vegetable intake level with academic achievement among school children age 9-11 years old in Kelantan. Two hundreds and seventy three ( 273), nine to eleven years of age, were randomly selected from three primary school in Kelantan. Physical activity level was assesed by using Physical Activity Questionnaire for Older Children ( PAQ-C). Fruit and vegetables intake level was assessed using Day- In-Life Questionnaire ( DILQ). Academic achivement of the respondants was recorded from their school final examination results in four subjects including Malay language, English, Mathematics and Science. BMI of the respondants was categorize according to body mass index-for -age percentile charts developed by World Health Organisation (2007) . There is higher number of children have normal BMI ( z-score) . Fruit and vegetable intake among the children is low. There is higher number of children in moderate physical activity level. The study showed that academic achievemet was not associated with fruit and vegetable intake level, physical activity and BMI.